Studying the Grignard reaction of qunazolinone derivatives containing an ester group - Shemchuk, L.A.; Levashov, D.V.; M. Al-Asri Jamil; Shenhof, Yu.O.; Arzumanov, P.S.; Chernykh, V.P. (Журнал органічної та фармацевтичної хімії, 2011)
The transformation of 4-oxo-3,4- dihydroquinazolinone derivatives containing an ester group under the conditions of the Grignard reaction has been investigated. It has been found that the reaction of 2-carbethoxy-4-oxo-3,4-dihydroquinazoline and (4-oxo-3,4-dihydroquinazolin-3-yl)-, (2-carbethoxy-4-oxo-3,4-dihydro-quinazolin-3-yl)acetic acid esters proceeds involving the ester group and the excess of the reagent does not influence on its result. Досліджено перетворення похідних 4-оксо-3,4-дигідрохіназоліну, які містять естерну групу, в умовах реакції Гриньяра. Встановлено, що реакція 2-карбетокси-4-оксо-3,4-дигідрохізоліну та естерів (4-оксо-3,4-дигідрохіназоліл)-, (2-карбетокси-4-оксо-3,4-дигідрохіназоліл)оцтовоїкислоти перебігає по естерній групі, надлишок реагента не впливає на перебіг реакції. Изучено превращение производных 4-оксо-3,4-дигидрохиназолина, содержащих сложноэфирную группу, в условиях реакции Гриньяра. Установлено, что реакция 2-карбэтокси-4-оксо-3,4-дигидрохиназолина и эфиров (4-оксо-3,4-дигидрохиназолил)-, (2-карбэтокси-4-оксо-3,4-дигидрохиназолил)уксусной кислоты протекает по сложноэфирной группе, избыток реагента не влияет на протекание реакции.